Pengelompokkan kabupaten/kota di Pulau Sulawesi berdasarkan indikator indeks khusus penanganan stunting menggunakan Gaussian mixture model - Rahman, Rezki; Junaidi, J.; Gamayanti, Nurul Fiskia (Jurusan Matematika FMIPA Universitas Jember, 2023)
Stunting or is a condition of growth failure in children under five years old (toddlers) who are malnourished. Children are called stunted if their height is below minus two standard deviations. The Special Index for Handling Stunting (IKPS) is one of the main indicators used as a measure of the achievement of handling the reduction in stunting rates. In implementing the 2024 development goals, namely setting a national stunting target that can decrease to 14%, it is necessary to identify based on the characteristics of a special index for handling stunting in each region. Method of Gaussian Mixture Model is a grouping with models that function to group a certain amount of data into a Gaussian distribution with mean and variance parameters. The main idea of model-based grouping is that object grouping is done using probabilities. This study was conducted with the aim of obtaining the results of grouping regencies/cities on Sulawesi Island based on the Special Index Indicator for Handling Stunting. The results of the study obtained different volume and shape models, coordinate axis orientation (VVI) with 4 optimum cluster. Cluster 1 with a low stunting handling index contains 24 districts/cities, cluster 2 with a medium stunting handling index contains 21 districts/cities, cluster 3 with a high stunting handling index contains 13 districts/cities, cluster 4 with a very high stunting handling index contains 23 districts/cities.Keywords: Four optimum cluster, low, medium, high and very highMSC2020: 62A09